Загадкові севрюки: 2. Етнічна природа спільноти - Балушок, В. (Сiверянський лiтопис, 2016)
Аналіз джерел, які містять інформацію про севрюків, показує, що й українці (які мали тоді самоназву «русь» у множині та «русин» в однині), і росіяни («русские»), й білоруси сприймали їх як «не своїх», «чужих». Тобто севрюки XIV–XVII ст. виступали окремим етносом. Це був «земельний» етнос, характерний для часів Київської Русі, що зберігався так довго на українсько-російсько-білоруському порубіжжі. Анализ источников, которые содержат информацию о севрюках, показывает, что и украинцы (которые имели тогда самоназвание «русь» во множественном и «русин» в единственном числе), и русские, и белорусы воспринимали их как «не своих», «чужих». То есть севрюки XIV–XVII вв. являлись отдельным этносом. Это был «земельный» этнос, характерный для времен Киевськой Руси, кторый сохранялся длительное время на украинско-русско-белорусском пограничье. The information contained in the sources about Sevriuks demonstrates that both Belarusians and Russians, and Ukrainians (which at that time had the endonyms Rus in plural and Rusyn in singular) did not consider them their own people; to those nations the Sevriuks were strange and occasionally inimical. That is attested by the Belarusian annals The Bychowiec Chronicle (by the year 1402) and The Lithuanian and Samogitian Chronicle (by the year 1416), as well as by various Russian records, predominately of the XVIth century. Those documents present the Sevriuks as the people with the traditions, customs and modes of life distinct from the Belarusian, Russian, and Ukrainian ones. During the frontier wars and interethnic conflicts, all those nations also took the Sevriuks as enemies, while the latter treated the Ukrainians, Russians and Belarusians likewise. The attitude to the Sevriuks as the representatives of a different ethnic community is corroborated by anthroponymy represented in the materials of the censuses of Ukrainian lands and in the Russian and Belarusian sources. That is, the XIVth–XVIIth-century Sevriuks acted as a separate ethnic group. It was a land ethnic group of the Kievan Rus times, which due to circumstances have remained on the Ukrainian-Russian-Belarusian borderland. Inasmuch as at the time of appanage fragmentation, each land (which corresponded with the concept of country and embodied one or more principalities, and which Kievan Rus was composed of), was populated by its own land ethic group. Although the northern (Russian) chronicles, on the grounds of spreading in Siverian land of the ethnonyms derived from Rus, affirm that the population of Sivershchyna has participated in ethno-consolidation processes that culminated in the XIIIth–XIVth centuries with the formation of the Ukrainians, Russians and Belarusians, the Sevriuks as a separate ethnic group had persisted as far as the XVIIth century, for all that.